Hypersensitivity reactions associated with oxaliplatin and their clinical management. (November 2014) - Toki, Maria I; Saif, Muhammad Wasif; Syrigos, Kostantinos N
<x xml:space="preserve">Abstract</x> Introduction: <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=Oxaliplatin&logicalOpe1=OR&field2=articletitle&text2=Oxaliplatin&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">Oxaliplatin, has become an integral part of the medical treatment of colorectal cancer and other malignancies. Increased use of the drug during the last decade, has led to increased occurrence of oxaliplatin-induced hypersensitivity reactions (HSRs), posing a significant challenge for clinicians. This article aims to review the existing literature regarding the incidence, clinical presentation, pathophysiology, risk factors and current management of oxaliplatin-induced HSRs. Areas covered: A systematic review of the English literature published in PubMed and Medline was undertaken. The clinical manifestations of HSRs were found to be variable and unpredictable. These reactions should be an important concern, as their potential life-threatening risks can force doctors to stop treatment and seek alternatives, which may be less effective, not as well tolerated and/or more expensive. There are a few strategies to prevent these reactions so that patients can still benefit from oxaliplatin. Such strategies include the use of premedication (steroid and antagonists of type I and II histamine receptors), prolonged infusion time and desensitization. Expert opinion: The presented management strategies as well as novel diagnostic tools including skin/intradermal tests and specific IgE have shown promising results. However, future research and validation are warranted in bigger clinical trials.